1990
DOI: 10.1029/jd095id11p18547
|View full text |Cite
|
Sign up to set email alerts
|

Rate of reaction of IO radicals with dimethylsulfide

Abstract: The kinetics of the title reaction have been investigated at 298 K using time‐resolved long‐pathlength absorption spectroscopy to monitor the temporal behavior of IO following 351‐nm laser flash photolysis of NO2/I2/CH3SCH3(DMS)/N2/O2 mixtures. We obtain an upper limit bimolecular rate constant for the IO+DMS reaction of 3.5×0−14 cm3 molecule−1 s−1; this upper limit is nearly 3 orders of magnitude slower than two previously reported measurements. Our results suggest that coupling of the marine sulfur and iodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 28 publications
6
32
1
Order By: Relevance
“…The present re-investigation of the reaction of I0 with DMS has shown that its rate constant is much lower than that we have previously measured and this is in agreement with the recent work of Daykin and Wine [6]. A low rate constant has also been found for the reaction of I0 with CH3SH while no reactivity has been observed between I0 and C2H4 or C3H6.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The present re-investigation of the reaction of I0 with DMS has shown that its rate constant is much lower than that we have previously measured and this is in agreement with the recent work of Daykin and Wine [6]. A low rate constant has also been found for the reaction of I0 with CH3SH while no reactivity has been observed between I0 and C2H4 or C3H6.…”
Section: Resultssupporting
confidence: 92%
“…1) x lo-'' cm3 molecule-' s-'. However, in a more recent laser photolysis-long path absorption study, a much lower rate constant value was found; an upper limit of 3.5 x crn3 molecule-' s-' was reported [6]. Considering this discrepancy, we have performed additional experiments on the I0 + DMS reaction.…”
Section: Introductionmentioning
confidence: 88%
“…However, recent measurements (Daykin and Wine, 1990) indicate that the rate of reaction is very slow, this reaction has therefore been neglected in the calculations.…”
Section: Emissionsmentioning
confidence: 99%
“…Oxidation of DMS and H 2 S by OH proceeds on time scales of hours to a few days; oxidation by Cl could be a more rapid sink for DMS in the marine boundary layer if large amounts of Cl are generated by reaction of O 3 with sea salt [Keene et al, 1991]. The possible importance of IO as a DMS oxidant has been recently downplayed by kinetic measurements indicating that the reaction is slow [Daykin and Wine, 1990]. A minor branch of DMS oxidation by OH produces methanesulfonic acid (MSA), and there has been some interest in using MSA/sulfate ratios as a signature of biogenic sulfate over the tropical and subtropical oceans [Savoie and Prospero, 1989].…”
Section: Sulfurmentioning
confidence: 99%